2010
DOI: 10.1080/07347332.2010.516810
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Anxiety and Depression Over Time Following Diagnosis in Patients with Prostate Cancer

Abstract: To determine the presence and nature of variability in anxiety and depression in patients with prostate cancer (PCa) over 3 years following diagnosis, 442 patients with PCa completed standardized anxiety and depression inventories via survey between 1 and 36 months after receiving their initial diagnosis. Data were analyzed from a series of 3-month cohorts, and results indicated that total scores and incidence of clinically significant anxiety and depression varied over time, but that this variability was rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…Those data suggest that PCa patients exhibit different depressive profiles at different times following their diagnosis, arguing for variability in treatment protocols also. As reported in a previous study [39], the "one size fits all" treatment approach suffers in the face of changing depressive profiles during the three years after initial PCa diagnosis, and may need to be more closely aligned to the kinds of symptom variability shown in Figure 1. While Figure 1(a) can inform therapists about the 'danger' periods for Melancholia, Anhedonia and Agitation, Figure 1(b) may also provide some planning suggestions regarding the comparative attention to be given to the Anhedonia vs Agitation aspects of Melancholia in PCa patients.…”
Section: Discussionmentioning
confidence: 98%
“…Those data suggest that PCa patients exhibit different depressive profiles at different times following their diagnosis, arguing for variability in treatment protocols also. As reported in a previous study [39], the "one size fits all" treatment approach suffers in the face of changing depressive profiles during the three years after initial PCa diagnosis, and may need to be more closely aligned to the kinds of symptom variability shown in Figure 1. While Figure 1(a) can inform therapists about the 'danger' periods for Melancholia, Anhedonia and Agitation, Figure 1(b) may also provide some planning suggestions regarding the comparative attention to be given to the Anhedonia vs Agitation aspects of Melancholia in PCa patients.…”
Section: Discussionmentioning
confidence: 98%
“…Improved survival brings the problems of cancer survivorship into focus. In particular, between 15% and 26% of survivors experience clinically significant anxiety and depression 3 to 5 years following treatment …”
Section: Introductionmentioning
confidence: 99%
“…Thus, symptom occurrence and any effects of those symptoms on anxiety or depression will not be captured in research that measures predictors shortly after diagnosis or treatment. Posttreatment symptoms and functional problems predict anxiety and depression symptoms in cross‐sectional studies, but cross‐sectional designs cannot show causality. We are not aware of prospective research that tests whether posttreatment symptoms and functional problems are linked to long‐term anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in several previous studies, we have found that there are different relationships found between various factors of the combined SAS-SDS "anxiety-depression" construct and PCa (Sharpley et al, 2010b;Sharpley & Christie, 2007a). Those investigations with larger samples of PCa patients revealed four underlying factors in the SAS-SDS scores of this population, labeled as Fear and Sadness, Psychological Agitation and Pessimism, Fatigue, Pain and Discomfort, and Physiological Arousal (Sharpley, Christie, & Bitsika, 2010), and the association between reported hormonal side effects and these SAS-SDS factors was investigated here to further clarify the effects that these side effects had upon the PCa patients sampled who reported such side effects.…”
Section: Resultsmentioning
confidence: 85%
“…This group of symptoms from the SAS-SDS combination reflects the kinds of psychological disquiet and lack of confidence that PCa patients may have about the likely outcome of their treatment and of their future health (Sharpley et al, 2010). That is, apart from the unpleasantness of their treatment (e.g., AAT side effects), this factor represents the absence of a sense of focus and optimism that these patients might experience regarding their overall PCa treatment and their future lives.…”
Section: Discussionmentioning
confidence: 93%